2019
DOI: 10.1590/1413-812320182412.23232019
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal austerity and the health sector: the cost of adjustments

Abstract: Fiscal austerity policies have been used as responses to economic crises and fiscal deficits in both developed and developing countries. While they vary in regard to their content, intensity and implementation, such models recommend reducing public expenses and social investments, retracting the public service and substituting the private sector in lieu of the State to provide certain services tied to social policies. The present article discusses the main effects of the recent economic crisis on public health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
(45 reference statements)
0
28
0
7
Order By: Relevance
“…North-American studies from the National Alcohol Survey, using the binge drinking indicator, found increased risk of alcohol consumption among women with college education or higher 33 . There are also the effects of economic and political crisis in the health indicators 34 , since the reduction of income and REV BRAS EPIDEMIOL 2021; 24: E210022.SUPL.1 unemployment can reduce the expenses with alcohol, especially in the populations that are mostly affected economically 25,35,36 . On the other hand, the pathological suffering and the stress caused by reduced income and unemployment may lead to more alcohol consumption 35 .…”
Section: Discussionmentioning
confidence: 99%
“…North-American studies from the National Alcohol Survey, using the binge drinking indicator, found increased risk of alcohol consumption among women with college education or higher 33 . There are also the effects of economic and political crisis in the health indicators 34 , since the reduction of income and REV BRAS EPIDEMIOL 2021; 24: E210022.SUPL.1 unemployment can reduce the expenses with alcohol, especially in the populations that are mostly affected economically 25,35,36 . On the other hand, the pathological suffering and the stress caused by reduced income and unemployment may lead to more alcohol consumption 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the country's economic crisis, it is necessary to value social rights together with economic growth, prioritizing action that targets the most vulnerable territories [50,53,[56][57][58][59]. The effects of economic crises in developing countries must be mitigated, prioritizing sustainable public funding of public services to the benefit of public welfare and progressively reducing potential health risks [60]. Greater investments are needed in social security, based on the BCE approach, in order to maximize human capital development (basic capabilities and personal potential), ensure adequate well-being, and fulfil the rights to health, education, social security and urban infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the country's economic crisis, it is necessary to value social rights together with economic growth, prioritizing action that targets the most vulnerable territories 50,53,[56][57][58][59] . The effects of economic crises in developing countries must be mitigated, prioritizing sustainable public funding of public services to the benefit of public welfare and progressively reducing potential health risks 60 .…”
Section: Survey With Household Heads Of Families In Extreme Povertymentioning
confidence: 99%